Variáveis morfológicas da cana-de-açúcar em função do regime hídrico durante o desenvolvimento inicial - De Holanda, Lucas Almeida [UNESP]; Santos, Claudiana Moura; Sampaio Neto, Givaldo D.; Sousa, Antônio De Pádua [UNESP]; Silva, Marcelo De Almeida [UNESP] (My University, 2014)
Water deficit is one of the factors which most limit agriculture yield and growth. Although sugar cane has moderate tolerance to drought, it presents high yield losses under the influence of this abiotic factor. Based on this fact, selection of genotypes tolerant to water stress may represent an alternative for decreasing the amount of water used for irrigation, while keeping or increasing yield. This study was performed in order to evaluate the performance of four sugarcane cultivars during initial development under water stress conditions, by means of morphological variables to select more tolerant genotypes to drought. The experiment was carried out in a greenhouse at the Department of Rural Engineering, College of Agricultural Sciences - UNESP/Botucatu – SP, from November 26th 2010 to April 5th 2011. A total of four sugar cane cultivars were evaluated (RB855453, RB92579, RB965902 and RB965917) under two treatments as follows: control (100% field capacity) and water stress (50% field capacity). Evaluations were performed at 0, 28 and 63 days after treatment application. The following morphological variables were analyzed: plant height, leaf area, leaf length, leaf width, number of green leaves, shoot and root dry matter. The RB855453 and RB92579 cultivars produced more shoot and root dry matter under water stress treatment, while the RB965902 and RB965917 cultivars had lower shoot and root dry matter production under the same conditions. Therefore, the RB855453 and RB 92579 cultivars can be considered tolerant while the RB965902 and RB965917 cultivars can be considered susceptible.
Morphological variables of sugar cane as a function of the water regime during initial development
Keywords: Cultivar; Drought; Morphological characteristics; Saccharum spp; Water stress